Distance Education from The Teachers' Perspective - Klaudia SMOLĄG (Communications of International Proceedings, 2022)
Until the outbreak of the Covid-19 pandemic, distance education was not common in Polish schools. Therefore, conducting classes remotely was quite a challenge for many teachers, especially at the level of primary and secondary schools. At Polish universities, remote classes in the form of e-learning classes were also conducted before the Covid-19 pandemic, but as an additional, alternative form of teaching. The outbreak of the Covid-19 pandemic forced classes to be conducted remotely, which in turn required both students and teachers to access computer equipment, applications and an Internet connection. It was possible only through the comprehensive use of information and communication technologies, which are currently the basis for the implementation of didactic processes. The purpose of this article is to evaluate distance learning from the teachers' perspective. The results of the study made it possible to identify the challenges of distance education for teachers resulting from the implementation of 100% remote teaching processes and to indicate what support methods were used by teachers during the Covid-19 pandemic. The study was quantitative and was carried out with the use of a questionnaire on 111 respondents (teachers) in the period January-April 2022. The obtained results indicate that remote learning increased teachers' perception of their own competences. Teachers, despite the time that have passed since the outbreak of the pandemic, most often obtain knowledge about the possibility of using available ICT tools from the Internet and from other teachers.
Keywords: distance learning; e-learning; teachers